Legitimacy paradoxes in the globalizing community - L Y Bronzino (RUDN journal of Sociology, 2009)
Being the cornerstone of the contemporary political system, legitimacy, however, incorporates a number of discrepancies which block the endeavors to develop a rational form of government based on democracy. The article provides the analysis of the discrepancies involved.